2013
DOI: 10.1073/pnas.1310656110
|View full text |Cite
|
Sign up to set email alerts
|

TET1 plays an essential oncogenic role in MLL -rearranged leukemia

Abstract: The ten-eleven translocation 1 (TET1) gene is the founding member of the TET family of enzymes (TET1/2/3) that convert 5-methylcytosine to 5-hydroxymethylcytosine. Although TET1 was first identified as a fusion partner of the mixed lineage leukemia (MLL) gene in acute myeloid leukemia carrying t(10,11), its definitive role in leukemia is unclear. In contrast to the frequent downregulation (or loss-of-function mutations) and critical tumor-suppressor roles of the three TET genes observed in various types of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
198
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(217 citation statements)
references
References 59 publications
11
198
4
Order By: Relevance
“…Despite this, the role of TET proteins in cancer progression has been debated. Our findings presented here are linked with an oncogenic role for TET proteins; this is consistent with previous reports demonstrating that TET proteins are associated with prognostic epigenetic signature and the regulation for a set of important oncogenic targets (47,48). Reduced 5hmC level was found in some types of cancer as compared with corresponding normal tissue (49); however, the correlation of 5hmC level as well as the related enzyme-TET proteins with tumor grading in breast cancer has not been thoroughly dissected.…”
Section: Discussionsupporting
confidence: 93%
“…Despite this, the role of TET proteins in cancer progression has been debated. Our findings presented here are linked with an oncogenic role for TET proteins; this is consistent with previous reports demonstrating that TET proteins are associated with prognostic epigenetic signature and the regulation for a set of important oncogenic targets (47,48). Reduced 5hmC level was found in some types of cancer as compared with corresponding normal tissue (49); however, the correlation of 5hmC level as well as the related enzyme-TET proteins with tumor grading in breast cancer has not been thoroughly dissected.…”
Section: Discussionsupporting
confidence: 93%
“…The chimeric protein lacks the hydroxylase activity, as the cys-rich domain of TET1 that is essential for enzymatic activity is deleted ). Interestingly, studies demonstrated that TET1 is overexpressed in MLL-rearranged leukemia and that TET1 function is required for up-regulating the expression of MLL chimera oncogenic targets such as HOXA9, MEIS1, and PBX3 (Huang et al 2013a). Reconciling this requirement for TET1 in MLL-rearranged leukemias and the molecular consequence of the MLL-TET1 rearrangement and its interplay with endogenous TET1 has yet to be determined.…”
Section: Dna Methylation In Hematopoiesis and Hematological Cancersmentioning
confidence: 99%
“…These studies suggest that an unusual DNA methylation/demethylation dynamic may be attributable to the alteration of the epigenome and phenotype in leiomyoma. Interestingly, TET1 upregulation leading to a global increase in 5-hmC levels was also found in mixed lineage leukemia (MLL)-rearranged leukemia, 92 indicating that TET proteins may play an oncogenic role in certain tumors.…”
Section: Active Dna Demethylation In Uterine Leiomyomamentioning
confidence: 99%